Investigation of the sulphate‐induced freezing inhibition effect from CloudSat and CALIPSO measurements - Grenier, Patrick; Blanchet, Jean‐Pierre (Journal of Geophysical Research: Atmospheres, 2010)
The hypothesis according to which higher sulphate concentrations favor ice clouds made of larger ice crystals is tested using data sets from the CloudSat and Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) satellites. This is a potential consequence of the sulphate‐induced freezing inhibition (SIFI) effect, namely, the hypothesis that sulphates contribute to inhibit the onset of ice crystal formation by deactivating ice‐forming nuclei during Arctic winter. A simple index based on the backscattering at 532 nm and the color ratio from the CALIPSO lidar measurements is compared against in situ sulphate concentration time series and used as a proxy for this variable. An algorithm using the lidar data and the CloudSat radar microphysical retrievals is also developed for identifying cloud types, focusing on those supposedly favored by the SIFI effect. The analysis includes the effect of the lidar off‐nadir angle on the sulphate index and the cloud classification, the validation of the index, as well as the production of circum‐Arctic maps of the sulphate index and of the SIFI‐favored clouds fraction. The increase of the lidar off‐nadir angle is shown to cause an increase in the measured depolarization ratio and hence in the ability to detect ice crystals. The index correlates positively with both sulphates and sea salt concentrations, with a Pearson correlation coefficient ( ) varying from 0.10 to 0.42 for the different comparisons performed. Ultimate findings are the results of two correlation tests of the SIFI effect, which allow for a new outlook on its possible role in the Arctic troposphere during winter.